(untitled) (Journal of Innovation and Technology Polbeng Series on Informatics (INOVTEK Polbeng - Seri Informatika), 2026)
Current blockchain-based Learning Management Systems (LMS) are predominantly limited to partial certificate validation using ERC-721 and face significant scalability constraints and high transaction costs on Layer-1 infrastructures, failing to address the complete educational life cycle. This study proposes a novel end-to-end decentralized LMS architecture integrating the Manta Pacific Layer 2 network for cost efficiency, the ERC-1155 standard for bulk license management, and Livepeer/IPFS protocols for autonomous content distribution. Employing a prototyping method, system performance was evaluated on the Manta Pacific Sepolia Testnet through 97 transaction scenarios covering course creation, enrollment, and real-time progress tracking via the Goldsky Indexer. Testing parameters focused on gas efficiency, transaction latency, and data integrity. Test results demonstrate significant operational efficiency with an average gas cost of 260.899 wei per transaction and a stable average block confirmation time of 10.0 seconds. Forensic validation confirmed 100% data consistency between internal system logs and blockchain explorer trails, alongside the successful execution of an automatic, intermediary-free revenue split (90/10). The proposed architecture proves capable of overcoming cost and latency barriers in educational blockchain adoption, offering a transparent, accountable, and technically feasible infrastructure for institutional scale.